Acidentes com transportes hidroviários e os extremos meteorológicos no nordeste da Amazônia - SANTOS, Suanne Honorina Martins dos (Universidade Federal do Pará, 2019)
This study analyzed the accidents with waterway transport passengers and cargo in the period 2008 to 2013, as a result of extreme weather occurring in the northeast Amazon, often with serious consequences the structure of vessels and especially the loss of human life. Based on data from the Flagship of the Eastern Amazon Ports, referring to the investigation of accidents facts of navigation, can be characterized in that period these accidents occur more and the distribution of these accidents in time and space, through sub-areas called 1, 2 and 3, where they are ranked the most common accidents in Subarea 1 type shipwreck where the basin of Marajó is located with features of larger rivers, in Subarea 2 and 3 of collision type where the morphological characteristics of rivers are narrower as well, in addition to these results was obtained in relation to rainfall in the rainy season (December to May) as the most responsible for accidents occurring during this period that suffers strong influence of precipitation systems as the Intertropical Convergence Zone, Mesoscale Convective Systems, instability lines and vortex of Advanced Levels and the less rainy season (June to December) the wind is regarded as the main variable that causes accidents in the waterway mode, especially during the intensification of the northeast trade winds, which are a free atmosphere of instability, accidents tend to occur more frequently in the time from 12 to 24 hours. Thus, with the precipitation climatology with the National Institute of Meteorology data, one can show through the climatology of the precipitation field of study, decreased quantity of deeper into sub-areas of the continent. The wind in the less rainy period acts with greater intensity in Subarea 1, the highest number of victims focuses on children and adults, mostly with men. It also presented an approach based on the socioeconomic aspects inherent risks of naval vessels with steel hulls and wood, the latter being the reality of the Amazon, which ultimately victims the more people and have more easily collapse structure, thus being potential threat to safety of navigation of cargo and passengers taking into account socioeconomic characteristics, although the vessels with the highest number of accidents has been pushers ferries built in naval steel. In this sense, the primary aid weather forecasting may decrease the favorable conditions for the occurrence of accidents with waterways vessels, because the lack of atmospheric conditions by those who pilot vessels is notoriously poor, because this lack of knowledge the chances of accidents are high, influencing the socioeconomic aspects of passengers and owners of vessels navigating the rivers belonging to the Marajó Bay, Tocantins, Pará and Amazonas river, which were the waterways studied in this dissertation.